Pengalaman Informasi Orang Kalang Kendal Tentang Tradisi Kalang Obong Sebagai Warisan Budaya Tak Benda Tradisi Kalang Obong - Durotun Nur Laili; Yanuar Yoga Prasetyawan (Jurnal Ilmu Perpustakaan, 2025)
Culture is rapidly developing nowadays with easy access to diverse informationanywhere. However, this development impacts the information experience of the Orang Kalang regarding their culture. The exposure to new knowledge has led to the formation of different characters among the Orang Kalang in interacting with the Kalang Obong tradition. The Kalang Obong tradition remains rich in local wisdom and has been recognized as one of Warisan Budaya Tak Benda (WBTB) since 2018. This supports the aim of this research to understand and explain the information experience of the Orang Kalang in Kendal regarding the Intangible Cultural Heritage of the Kalang Obong tradition. The researcher employed a qualitative method with a phenomenological approach to accurately and systematically uncover the phenomena that occur. The data collection process was conducted through interview methods using snowball sampling techniques to obtain informants. Subsequently, the data was analyzed thematically. The study found three themes: the interpretation of the Kalang Obong tradition by the People of Kalang, the implementation of Kalang Obong knowledge, and the preservation of Kalang Obong knowledge. The first theme indicates that the essence of the Kalang Obong tradition has an influence based on the experiential information of the Kalang People. The second theme describes that the implementation of the Kalang Obong tradition is closely related to the commitment of the Kalang People and their environment. The third theme emphasizes that the peak of the existence of Kalang Obong tradition knowledge still requires efforts in knowledge preservation through education, legality, and documentation. The study can be further developed with a more specific topic.